Production model to improve the efficiency of a peruvian cotton knitwear export company using 5s, standardization of operations and autonomous maintenance - Baldeon-Lazaro, Thania (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.